Face and content validity of an artificial eye model for Ab-Interno Goniotomy. Issue 5 (September 2021) - Swift, Andrew; Waldner, Derek; Gorner, Adam; Chung, Helen; Ahmed, Yusuf; Docherty, Gavin; Gooi, Patrick
Purpose: To determine the face and content validity of an artificial eye model for ab-interno goniotomy (SimulEYE KDB model, InsEYEt, Westlake Village, CA) by surveying ophthalmologists with varying experience using a Kahook Dual Blade (KDB; New World Medical, Rancho Cucamonga, CA, USA) following a 90-min wet-lab course using the model. Participants: Overall 13 ophthalmologists participated following a surgical simulation session on goniotomy using the goniotomy blade at the 2019 Canadian Ophthalmological Society annual meeting. Methods: A 17-question survey to assess the face and content validity of the model was given immediately following the surgical simulation session on goniotomy using the goniotomy blade. Responses to each survey question were recorded on a 5-point Likert scale ranging from (1) strongly agree to (5) strongly disagree. Results: Respondents rated statements regarding the model with a median response of 1 (Strongly Agree) to 3 (Neither agree or disagree). Mann–Whitney U nonparametric analysis revealed no significant difference in responses between instructor vs. non-instructor or between prior experience vs. no prior experience for any of the survey statements. The model received highest survey ratings for utility in training residents, acquisition of surgical skills, accessibility, and higher likelihood of success with the procedure than theory and observation alone. Lowest ratings were for realism of the model compared to a human cadaveric eye. Conclusion: Our results suggest the SimulEYE KDB model is a reasonably cost-effective solution for simulating angle-based surgeries. Additionally, our project shows that experienced ophthalmologists found the artificial eye models useful and helpful for angle-based surgery training.